A Life With Purpose : Reverend Rick Warren, The Most Inspiring Pastor of our Time - Mair, George (New York Berkley Books, 2005)
A biography of the man called "America's most influential pastor" furnishes a study of the life of Rick Warren, discussing what prompted him to begin preaching, his family life, his visionary mission, and his influential work, "The Purpose-Driven Life," and its message.
The Most Inspiring Pastor of our Time.
Keywords: United States -- Warren, Richard, 1954- -- Christian biography -- Clergy